Vernicular and classical Arabic in the perspective of Mohebedine Al Khatib - Cherif Hocine , Mohammed (Journal of Social Sciences and Humanities, 2021)
Mohebedine Al Khatib is one of the great thinkers who defender the arabic and islamic nation, and confronted the westernisation wave that engulfed it since the beginning of the last century. Including call to use vernicular instead of clssical arabic and to write it in latin letters. Many of debaters have called to this invitation like Lotfi Essaîd and Salama Moussa who adopted William Wilcok’s call. A lot of orientalists have called to these ideas before, like frensh orientalists Massignon and Baniar. These claims have sparked a number of writers and scholars by respondingto, and strongly opposing them. Mohebedine El Khatib considered them a waste of time and nation ressources, and a strike for the national psyche. He was supported by a lot of thinkers and intellectuals like Mohamed Assadik Arrafii, Rachid Redha, Chakib Arslan and many others.